Rview of the article summary and summary techniques applied to the article on family agriculture - Araújo, Daniel Silva de; Macedo, Aurilene Alves de; Souza, Lorena da Silva de (Revista Coleta Científica, 2018)
This is a review of the article entitled, Synthesis and Summary Techniques Applied to an Article on Family Farming. This article is authored by: Jonas Rodrigo Gonçalves. The article reviewed here was published in the jornal Agro em Questão: Journal of Scientific Initiation of Faculdade CNA, in Year II (2018), Vol. II, n. 03.